1986
DOI: 10.1254/jjp.42.345
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcitonin Gene-Related Peptide on the Cyclic AMP Level of Isolated Mouse Diaphragm

Abstract: Abstract-The effect of calcitonin gene-related peptide (CGRP) on the cyclic nucleotide level in isolated mouse diaphragm was investigated.CGRP at con centrations of up to 1 i M caused dose-dependent increases in cyclic AMP levels but had no effect on cyclic GMP levels. At 1 /tM, CGRP increased cyclic AMP levels by about 2.7-fold.Moreover, in the presence of phosphodiesterase inhibitor (Ro 20-1724), CGRP still caused even greater dose-dependent increases in cyclic AMP levels. Even in the presence of propranolol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

1987
1987
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 16 publications
1
30
0
Order By: Relevance
“…In a recent report, Correia-de-Sa & Ribeiro (1993) showed that facilitation of evoked [3H]-ACh release from the phrenic-diaphragm preparation by an activator of the catalytic subunit of adenylate cyclase, forskolin, depends on A2a-adenosine receptor activation by endogenous adenosine. Calcitonin gene-related peptide (CGRP) is co-secreted with ACh at the motor endplates of mammals (Rodrigo et al, 1985;Takami et al, 1985), and increases ACh release apparently through stimulation of adenylate cyclase activity (Kobayashi et al, 1987;Mullholland & Jaffer, 1990) increasing intracellular accumulation of cyclic AMP (Takami et al, 1986). It were also examined.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…In a recent report, Correia-de-Sa & Ribeiro (1993) showed that facilitation of evoked [3H]-ACh release from the phrenic-diaphragm preparation by an activator of the catalytic subunit of adenylate cyclase, forskolin, depends on A2a-adenosine receptor activation by endogenous adenosine. Calcitonin gene-related peptide (CGRP) is co-secreted with ACh at the motor endplates of mammals (Rodrigo et al, 1985;Takami et al, 1985), and increases ACh release apparently through stimulation of adenylate cyclase activity (Kobayashi et al, 1987;Mullholland & Jaffer, 1990) increasing intracellular accumulation of cyclic AMP (Takami et al, 1986). It were also examined.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Additional ligands capable of inducing or inhibiting cAMP signaling in muscle cells include calcitonin gene-related peptide (CGRP) (173,222,223), corticotropin-releasing factor (CRF) (124,179), interleukin-6 (IL-6) (118), adenosine (152), prostaglandin E 1 (247), Arg 8 -vasopressin (AVP) (167), and numerous chemokine receptors such as CXCR4 (CXC chemokine receptor 4) (79) and Wnts (39). There are undoubtedly additional ligands that induce or repress cAMP signaling in skeletal muscle.…”
Section: (See Hypertrophy and Injury And Regeneration)mentioning
confidence: 99%
“…Only a few primary messengers possibly involved in the regulation of the cyclic AMP level of skeletal muscle have been established. Calcitonin gene-related peptide, a peptide that is co-released with acetylcholine-(ACh) at the neuromuscular junction (Changeux, 1991), elevates intracellular levels of cyclic AMP (Mulle et al, 1988) and induces the related desensitization (Takami et al, 1986) and up-regulation (Fontaine et al, 1987) of nicotinic AChRs.…”
Section: Introductionmentioning
confidence: 99%